Consumo responsável e mobilização social: estudo de caso da dinâmica comunicacional da Rede Ecológica do Rio de Janeiro - Santos, Nádia Bernuci dos (2013)
This dissertation addresses the dynamics of information flows in a network of responsible consumption. With a broad perspective that the ecological question emerges showing the unsustainability of the system of capitalist production and consumption compared to the depletion of natural resources. The topic of research approaches aspects associated with consumption as an important operator that capitalist growth model, raising the debate of the formation of movements opposed to consumerism and mobilized for transformation through a social practice that goes against the logic of the capitalist market. In this sense, this work aimed to raise some groups that operate in Brazil, motivations and identify their causes and to propose different categories of groups, that have in common the opposition to consumerism and support environmental causes. Thenceforth, the dissertation selected for the preparation of a case study of a group of activists who organized a movement called Rede Ecológica. This case study sought to identify, through a mapping of internal and external flows of information in dynamic communication network. To perform this research we used the Social Network Analysis which was based on data obtained through interviews and surveys in loco. Without claiming to represent the set of social movements in Brazil, which in many ways act against consumerism, the case study describes one of the final links in a debate that begins with the ecological crisis. In this sense, a contribution of this dissertation may be to mark with one of the possible directions and necessary to face the ecological crisis, in addition to public policy, where the spontaneous and autonomous organization of people gathered around common causes, acts as incubators new projects of society